2016
DOI: 10.1128/jcm.02723-15
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes: Disease-Causing Agent or Common Contaminant? Detection in Diverse Patient Samples by Next-Generation Sequencing

Abstract: Propionibacterium acnes is the most abundant bacterium on human skin, particularly in sebaceous areas. P. acnes is suggested to be an opportunistic pathogen involved in the development of diverse medical conditions but is also a proven contaminant of human clinical samples and surgical wounds. Its significance as a pathogen is consequently a matter of debate. In the present study, we investigated the presence of P. acnes DNA in 250 next-generation sequencing data sets generated from 180 samples of 20 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 50 publications
3
66
0
3
Order By: Relevance
“…Next, we investigated whether specific bacterial taxa that have previously been reported to be likely contaminants are present in our data set. Following read-based analyses, we found that our samples were dominated by Cutibacterium (Propionibacterium) acnes, which is abundant on human skin (Byrd et al, 2018) and a known contaminant of high-throughput sequencing data (Lusk, 2014;Mollerup et al, 2016). We therefore investigated the distribution of sequence identity between our C. acnes reads and the C. acnes reference genomes, with the expectation that human or laboratory contaminants would show high (close to 100) percentage identity, whereas killer whale-derived C. acnes would be more divergent.…”
Section: Known Bacterial Contaminantsmentioning
confidence: 97%
“…Next, we investigated whether specific bacterial taxa that have previously been reported to be likely contaminants are present in our data set. Following read-based analyses, we found that our samples were dominated by Cutibacterium (Propionibacterium) acnes, which is abundant on human skin (Byrd et al, 2018) and a known contaminant of high-throughput sequencing data (Lusk, 2014;Mollerup et al, 2016). We therefore investigated the distribution of sequence identity between our C. acnes reads and the C. acnes reference genomes, with the expectation that human or laboratory contaminants would show high (close to 100) percentage identity, whereas killer whale-derived C. acnes would be more divergent.…”
Section: Known Bacterial Contaminantsmentioning
confidence: 97%
“…Besides the problem posed by the human DNA, also external bacterial contamination has to be considered before defining a microbial-disease causation. [52,53] The choice of the DNA extraction method is similarly important. Frequently, commercially available kits are used with popular choices being the Qiagen DNA Extraction Kit (Qiagen GmbH, Hilden, Germany), [12,47] the MO BIO PowerSoil DNA Isolation Kit (MoBio Laboratories, Inc., Carlsbad, CA) [5,17,54] or the MO BIO Ultraclean…”
Section: Sample Collection and Dna Extraction Proceduresmentioning
confidence: 99%
“…For confirmation of this hypothesis, healthy donors need to be recruited from the same population as the GC patients. P. acnes has been proposed as a possible contaminant of many experiments [Mollerup et al 2016]. That does not mean we need to discard the bacterium altogether, notably not if it shows significant increase in tumor sample locations as in data sets SRP172818 and SRP128749, but it could mean its baseline presence is overestimated and hence its status as a gastric mucosa commensal [Delgado et al 2011].…”
Section: Discussionmentioning
confidence: 99%